CHILD PROTECTION IN THE FAMILY ENVIRONMENT BASED ON SHARI'AH VALUES - riska, Jumita; Wani, Wani; Hasanah, Uswatun (AS-SAIS (JURNAL HUKUM TATA NEGARA/SIYASAH), 2025)
ABSTRACT:Marriage constitutes a legally recognized institution for establishing a family and procreating, aligned with human nature. Every marriage inherently embodies significant expectations, notably the birth of children to perpetuate the family lineage. Having offspring is a universal aspiration for married couples. The presence of children fosters a harmonious marital relationship, as spouses collaboratively provide love, support and care. Children's arrival strengthens the bond between spouses, fostering shared responsibility for nurturing, upbringing and mutual affection. A child undergoes developmental stages from infancy to adulthood, ultimately becoming self-sufficient. Parents bear responsibility for providing necessities, education and guidance. Beyond basic care, instilling Islamic values (Syari'ah) is crucial, enabling children to embody these principles, ensuring their well-being and protection throughout adulthood.Keywords: Child; Protection; Syari'ah.